2020
DOI: 10.1186/s13287-020-01719-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional culture of MSCs produces exosomes with improved yield and enhanced therapeutic efficacy for cisplatin-induced acute kidney injury

Abstract: Background: Exosomes derived from mesenchymal stem cells (MSC-exos) have been demonstrated with great potential in the treatment of multiple human diseases including acute kidney injury (AKI) by virtue of their intrinsic cargoes. However, there are major challenges of low yield and the lack of an established biomanufacturing platform to efficiently produce MSC-exos, thereby limiting their therapeutic application. Here, we aimed to establish a novel strategy to produce MSC-exos with a hollow fiber bioreactor-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(172 citation statements)
references
References 50 publications
5
153
0
Order By: Relevance
“…Human umbilical cord mesenchymal stem cells (hucMSCs, donated by Wingor Biotechnology Co, Ltd) were cultured with media mixed with mesenchymal stem cell medium (ScienCell) and DMEM/F12 (Gibco), supplemented with 5% fetal bovine serum (FBS; ScienCell). The identification of hucMSCs was determined as previously described 16 . To prepare MSC-exos, hucMSCs (Passage 2-6) were cultured with FBS-free media for 48 h, and the supernatants were subsequently collected for MSC-exos extraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human umbilical cord mesenchymal stem cells (hucMSCs, donated by Wingor Biotechnology Co, Ltd) were cultured with media mixed with mesenchymal stem cell medium (ScienCell) and DMEM/F12 (Gibco), supplemented with 5% fetal bovine serum (FBS; ScienCell). The identification of hucMSCs was determined as previously described 16 . To prepare MSC-exos, hucMSCs (Passage 2-6) were cultured with FBS-free media for 48 h, and the supernatants were subsequently collected for MSC-exos extraction.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that EVs derived from MSCs have been proposed as an alternative to MSC-based therapy for several diseases 15 . In the previous study, we found that exosomes derived from MSCs (MSC-exos) could significantly attenuate cisplatin-induced murine AKI through inhibiting inflammation 16 . Although the exact mechanisms are largely assumptive, anti-inflammation, anti-apoptosis, immunomodulation, and promoting proliferation are all conducive to the treatment of AKI 17 .…”
Section: Introductionmentioning
confidence: 99%
“…19.4 times [42,43]. Moreover, compared with 2D-sEVs, 3D-sEVs has no signi cant differences in surface markers, size, and shape.…”
Section: Discussionmentioning
confidence: 89%
“…And in combination with the conventional differential ultracentrifugation, threedimensional (3D) culture based on scalable microcarrier yields 20-fold more exosomes. Similarly, Cao et al investigated a strategy to increase total MSC-exosome production to 19.4-fold with a hollow fiber bioreactor-based 3D culture system and evaluated the therapeutic efficacy of 3D-exosomes om AKI [90]. They reported that 3D culture did not significantly change the surface markers of MSCs, as well as the morphology, size, and exosomal markers.…”
Section: Unsolved Frontiersmentioning
confidence: 99%